Concomitant Intravitreal Ganciclovir and Dexamethasone Therapy in the Management of Acute Retinal Necrosis in a Patient Previously Treated with Oral Famciclovir - Chirag V. Patel; Kamal Kishore (Case Reports in Ophthalmological Medicine)
Several treatments have been reported for acute retinal necrosis (ARN). We report a case of treatment with intravitreal injection of ganciclovir and dexamethasone in addition to oral valacyclovir in a patient who was previously treated with oral famciclovir for ipsilateral herpes zoster ophthalmicus (HZO).